DYNAMIC CHANGES IN INFLAMMATORY INDICES AFTER LAPAROSCOPIC COMMON BILE DUCT EXPLORATION IN MALE AND FEMALE PATIENTS WITH COMPLEX COMMON BILE DUCT STONES - V.V. Volkovetskii; O.M. Lobanova; N.V. Puzyr; A.E. Tkachenko; M.V. Maksimenko; Ya.M. Susak; L.M. Skivka (Biotechnologia Acta, 2025)
Common bile duct stones (CBDS) are among the most prevalent biliary tract diseases, with a higher incidence in women, and pose a significant global health challenge. If left untreated, CBDS can lead to severe inflammatory complications, including cholangitis, pancreatitis, and biliary cirrhosis. Laparoscopic common bile duct exploration (LCBDE) followed by laparoscopic cholecystectomy (LC) has become a widely adopted treatment approach, alongside advanced endoscopic retrograde cholangiopancreatography (ERCP) techniques. However, managing cholelithiasis accompanied by difficult common bile duct stones (DCBDS) remains particularly challenging. The LCBDE + LC approach has been shown to minimize surgical trauma and systemic inflammatory response, leading to faster recovery in patients with cholelithiasis accompanied by DCBDS. Despite these advancements, sex-based differences in post-LCBDE + LC systemic inflammatory response remain largely unexplored.